Hebella striata Allman 1888 - Galea, Horia R.; Schories, Dirk; Försterra, Günter; Häussermann, Verena (Zenodo, 2014)
Hebella striata Allman, 1888 (Fig. 1 C, D) Material examined . HF7, Remolina, lat. -41.80727, long. -73.52517, 23.i.2009, 23 m, sample B244: colony on Eudendrium sp., several gonothecae present (MHNG-INVE-86207). HF16, East of Seño Contreras, lat. -50.34242, long. -75.2259, 24.iv.2013, 22 m, sample 579: colonies on Symplectoscyphus filiformis (Allman, 1888) and Lafoea dumosa (Fleming, 1828), one gonotheca found (MHNG-INVE-86206). Remarks . Details on the trophosome of this species have been given in an earlier account (Galea 2007). Several gonothecae occur in the present material. They are large, tubular, tapering gradually basally into an indistinct pedicel of varied length. Distally truncated and covered by a thin layer of perisarc that is ruptured upon release of the gonophore, thus producing a four-flapped “operculum”. Elsewhere, the perisarc is transversely wrinkled, but the striations are coarser than on the hydrotheca, and fade off basally. In order to preserve the integrity of samples, only the depicted gonotheca (Fig. 1 D) was measured: it is 2220 µm long and 510 µm wide just above the aperture. There is one gonophore per gonotheca, and no morphological details could be observed in this fairly well preserved material. In contrast, Hartlaub (1905) figured several medusa buds in a conspicuously curved gonotheca. Distribution in Chile . The northern limit of this species is probably the Ancud Gulf and the Calbuco Channel (Leloup 1974), while it reaches Tierra del Fuego in the South (Hartlaub 1905). World records . A subantarctic and Antarctic species (Vervoort 1972, Millard 1977). Published as part of Galea, Horia R., Schories, Dirk, Försterra, Günter & Häussermann, Verena, 2014, New species and new records of hydroids (Cnidaria: Hydrozoa) from Chile, pp. 1-50 in Zootaxa 3852 (1) on page 6, DOI:10.11646/zootaxa.3852.1.1, http://zenodo.org/record/286956